Sex estimation using subpubic angle from reconstructed three-dimensional computed tomography pelvic model in a contemporary Malaysian population - Siti Hanum Mohd Ali; Normaliza Omar; Shafie M.S.; Ismail N.A.N.; Hadi H.; Nor F.M. (Korean Association of Anatomists, 2024)
Indexed by WOS/SCOPUS